THE EFFECT OF POC TOFU WASTEWATER PRODUCTION ON GROWTH AND YIELDS OF EDAMAME SOYBEAN (Glycine Max (L.) Merill) - Untung Santoso; Devi Asriyanti; Antar Sofyan (Universitas Lambung Mangkurat, 2021)
Edamame (Glycine max (L.) Merill) is one type of soybean plant that has a high selling value. Edamame production in South Kalimantan is still low compared to other regions, this has become one of the opportunities to develop this edamame plant. Dependence on the use of inorganic fertilizers is still a problem in crop cultivation, thus the need for innovation excessive use of inorganic fertilizers by utilizing liquid organic fertilizers. Tofu industrial plants have waste which has a negative impact on the air and water around the factory, this is a consideration for make tofu liquid waste as liquid organic fertilizer. This study aims to determine the effect of tofu POC liquid waste on growth and yield, as well as determine the best dose. This research was conducted in the area of Jl. Trans Gunung Kupang, Kec. Cempaka, Banjarbaru City, South Kalimantan in May to July 2019. The method used is one-factor Randomized Block Design (RCBD), with 7 handling doses that were repeated 4 times to obtain 28 experimental units, namely: K0- (control), K0 + fertilizer 7% liquid chemistry (3.5 ml per 50ml water), 4% K1 (2 ml per 50 ml water), 5% K2 (2.5 ml per 50 ml water), 6% K3 (3 ml per 50 ml water) ), K4 7% (3.5 ml per 50 ml water) and K5 8% (4 ml per 50 ml water). The results shows that the administration of liquid tofu waste POC significantly react plant growth, namely plant height and number of leaves, as well as the yield of wet pod weight, the best dose to increase plant growth and yield was 7% K4 (3.5 ml per 50 ml of water) .